PSIX-18 Effect of chicory silage and se-yeast on peripartum ewes: Immune status via complete blood cell count. (8th October 2021) - Ford, Hunter; Bionaz, Massimo; Ates, Serkan; Hasan, Daniella; Klopfenstein, Joe; Park, Shelby; Quinones, Tyler; Pearce, Carolyn; Ness, Kate; Torres, Mariangel Aleman
Abstract: Immune status is critical for peripartum animals. Immune cells are highly affected by the oxidative status and level of Se. The use of forages with high content of antioxidants in combination with Se-yeast can improve the immune status in peripartum ruminants. The objective of this study was to test the possibility of improving the immune system of peripartum ewes by feeding a combination of chicory silage and Se-yeast. Approximately one month prior to lambing, 36 pregnant Polypay sheep were moved into single pens and randomly assigned to one of four groups to be fed either grass or chicory silage and supplemented or not with 3.6 mg Se/day (DiaMune, Diamond V). Blood was collected throughout the study to assess the complete blood count (VetScan HM5). Secondary compounds in silages were analyzed via LC-MS/MS. Data were analyzed using GLIMMIX (SAS) with day, silage type, Se and their interactions as fixed effects and ewe as random effect with significance declared at P≤0.05. Compared to grass silage, among measured secondary compounds only resveratrol was larger in chicory vs. grass. Total white blood cell count was larger in animals fed grass vs. chicory silage. Silage type and Se-yeast supplementation had little effects on the other measured parameters. The average hemoglobin inside red blood cells was larger in animals fed grass vs. chicory silage. Only tendencies (P between 0.08 and 0.09) were observed for the effects of Se supplementation, including increased hematocrit and number of circulating monocytes but, the latter, only in grass-fed ewes, and decreased red blood cell volume. Platelet size distribution tended (P=0.08) to increase in grass-fed ewes supplemented with Se but the opposite was observed in ewes fed chicory silage. Together, these data indicate a minimum-to-no effect of the type of silage or Se supplementation on complete blood cell count on peripartum ewes.